(untitled) (Homoeopathy for All, 2025)
In recent years, the field of Homoeopathy in India has undergone significant transformation, primarily driven by the establishment of the National Commission for Homoeopathy (NCH) in 2020. This regulatory body, created under the National Commission for Homoeopathy Act 2020, has spearheaded a series of reforms aimed at enhancing the quality and integrity of Homoeopathy education and practice. These changes promise to elevate the standards of Homoeopathy, ensuring its practitioners are well-equipped to meet contemporary healthcare challenges.